2014
DOI: 10.1161/hypertensionaha.114.04278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Antihypertensive Treatment on White-Coat Hypertension

Abstract: A large number of studies has provided information on the clinical characteristics of subjects with isolated office or white-coat hypertension (WCH). [1][2][3][4][5][6][7][8][9][10][11][12][13] However, information is limited on whether and to what extent WCH is affected by antihypertensive treatment. The limitation includes the effect of treatment on blood pressure (BP) because although some studies have reported that in WCH treatment lowers office BP, 14 other studies deny that this occurs, quoting as an exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
1
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 64 publications
6
21
1
2
Order By: Relevance
“…5 Regarding this fact, although some researchers suggest an association with higher CVR, the controversy on the benefit of treating such patients remains. 37 In our study, the prevalence of non-dipper profile (40%) was similar to the ones reported in other surveys (between 25% to 60%). 6,7 The occurrence of masked HBP (28% in our study) was relatively high, revealing the cases that are Considering nocturnal HBP as an important marker of CVR, 9,10 a significant prevalence (52%) was found in our study.…”
Section: Discussion and Conclusion Hbp Profiles And Controlsupporting
confidence: 91%
“…5 Regarding this fact, although some researchers suggest an association with higher CVR, the controversy on the benefit of treating such patients remains. 37 In our study, the prevalence of non-dipper profile (40%) was similar to the ones reported in other surveys (between 25% to 60%). 6,7 The occurrence of masked HBP (28% in our study) was relatively high, revealing the cases that are Considering nocturnal HBP as an important marker of CVR, 9,10 a significant prevalence (52%) was found in our study.…”
Section: Discussion and Conclusion Hbp Profiles And Controlsupporting
confidence: 91%
“…Consistent with an earlier report by Mahfoud et al [21], in patients with uncontrolled hypertension due to a white-coat effect, office BP was reduced but there was no effect of RDN on ambulatory BP. This pattern of treatment response in patients with-white coat hypertension is strikingly similar to that observed with longterm pharmacological interventions [40]. Whereas these observations suggest that the renal sympathetic nerves are not the prime driver in the generation of hypertension in these patients, other sympathetic neural outflows could be involved and may lead to a degree of end-organ dysfunction.…”
Section: Discussionsupporting
confidence: 74%
“…However, whether patients with WCH would be benefited from antihypertensive treatment remains unknown. It has been shown that antihypertensive treatment might lower clinic BP, rather than ABP [40,43]. A post-hoc analysis of a subgroup of patients from the Systolic Hypertension in Europe trial also showed that in WCH, antihypertensive treatment did not lower cardiovascular events [44].…”
Section: Discussionmentioning
confidence: 99%